Supervision for school psychologists in training: Developing a framework from empirical findings. (August 2016) - Gibbs, Simon; Atkinson, Cathy; Woods, Kevin; Bond, Caroline; Hill, Vivian; Howe, Julia; Morris, Sue
Similar to other professional disciplines, the importance of supervision within school psychology has attracted considerable attention within recent years. Despite this, systematic review of current literature reveals a dearth of empirical literature proposing underlying theoretical structures. This study extends recent qualitative research by surveying 310 school psychology students undertaking a preparatory doctoral training programme within the 12 approved universities in England and Wales. Data were obtained from a 21-item closed questionnaire developed from previous empirical findings and subjected to Exploratory Factor Analysis. Findings reveal three key supervisory components: Safe space for authentic learning, instructional support, and reference points for professional learning. Comparisons with other theoretical models are made and implications for practice explored. A framework for professional practice, based on key findings and other important theoretical developments, is proposed.